2021
DOI: 10.1007/s00204-021-03095-z
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin involvement in okadaic acid-induced diarrhoea in vivo

Abstract: The consumption of contaminated shellfish with okadaic acid (OA) group of toxins leads to diarrhoeic shellfish poisoning (DSP) characterized by a set of symptoms including nausea, vomiting and diarrhoea. These phycotoxins are Ser/Thr phosphatase inhibitors, which produce hyperphosphorylation in cellular proteins. However, this inhibition does not fully explain the symptomatology reported and other targets could be relevant to the toxicity. Previous studies have indicated a feasible involvement of the nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Results from in vitro studies had suggested that the potent pro-absorptive peptide neuropeptide Y (NPY) was altered after OA treatment in a neuroblastoma cell line [ 177 ]. However, NPY administration prior to OA did not modify OA-induced poisoning in mice, but in the same study, serotonin was directly involved in OA-induced diarrhea [ 178 ]. The secretory role of serotonin in the pathophysiology of diarrhea has been largely reported [ 176 , 179 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
See 2 more Smart Citations
“…Results from in vitro studies had suggested that the potent pro-absorptive peptide neuropeptide Y (NPY) was altered after OA treatment in a neuroblastoma cell line [ 177 ]. However, NPY administration prior to OA did not modify OA-induced poisoning in mice, but in the same study, serotonin was directly involved in OA-induced diarrhea [ 178 ]. The secretory role of serotonin in the pathophysiology of diarrhea has been largely reported [ 176 , 179 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
“…OMIC techniques may be a valuable tool in understanding OA-altered pathways [ 184 ]. After ingestion of DSTs-bearing bivalves, toxins are localized mainly at the gastrointestinal tissues [ 178 ]. They cause diarrhea stimulating Na + secretion by intestinal cells, leading to intraluminal gastrointestinal (GI) fluid accumulation and abdominal cramping [ 14 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PP inhibition by OA can both increase and reduce intestinal paracellular permeability [14,15], and increased paracellular permeability can cause fluid accumulation and diarrhea. Moreover, non-PP mechanisms involving neuropeptide Y and serotonin may also be mechanistically responsible for OA-induced diarrhea [16,17]. However, the mechanisms responsible for the toxicities of these compounds are poorly understood [13].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, diarrhea as an acute effect of OA is ascribed mainly to an increased phosphorylation level of proteins involved in ions secretion and of cytoskeletal/junctional elements of intestinal cells controlling paracellular permeability to solutes. This effect is assumed to cause a passive loss of fluids from the intestinal wall into the lumen, leading to diarrhea [8,[16][17][18][19], but other mechanisms have been also suggested [18,20].…”
Section: Introductionmentioning
confidence: 99%